Inhibition of SUR1-TRPM4 attenuates astrocyte swelling and reactivity under oxygen-glucose deprivation/reoxygenation - Yuanyuan Zhao; Narawut Pakaprot; Rujapope Sutiwisesak; Unchalee Vattarakorn; Sompol Tapechum (PLoS ONE, 2026)
Astrocytes play essential roles in maintaining brain homeostasis but undergo pathological alterations following ischemia-reperfusion (I/R) injury. Astrocyte swelling and reactive changes are associated with secondary injury processes, including cerebral edema and neuroinflammatory responses. In vitro injury models have demonstrated cellular swelling and stress-induced alterations in astrocytes. The sulfonylurea receptor 1-transient receptor potential melastatin 4 (SUR1-TRPM4) channel has been implicated in astrocyte swelling; however, its potential association with downstream stress-related signaling responses remains incompletely understood. In this study, CTX-TNA2 cells, a rat astrocyte cell line, were subjected to oxygen-glucose deprivation/reoxygenation (OGD/R) to model I/R injury. Cellular swelling, astrocyte reactivity, and cell viability were evaluated together with indicators of oxidative stress, endoplasmic reticulum stress, and STAT3-associated signaling responses. OGD/R induced cell swelling, increased GFAP expression, and reduced cell viability, accompanied by enhanced NOX4-related oxidative stress, activation of PERK-mediated endoplasmic reticulum stress signaling, and STAT3 activation. Pharmacological inhibition of SUR1-TRPM4 attenuated astrocyte swelling and those signaling cascades under OGD/R conditions, accompanied by reduced GFAP expression and improved cell viability. Modulation of individual stress pathways partially attenuated GFAP expression under OGD/R conditions. These findings suggest that SUR1-TRPM4 contributes not only to astrocytic swelling but also to astrocyte reactivity and cellular stress responses under in vitro ischemia-like conditions.